ARL4C depletion suppresses the resistance of ovarian cancer to carboplatin by disrupting cholesterol transport and autophagy via notch-RBP-Jκ-H3K4Me3-OSBPL5. (12th October 2022) - Yang, Juan; Peng, Shuping; Zhang, Keqiang
Increasing studies indicate that cholesterol plays an important role in drug resistance. ARL4C is implicated in the export and import of cholesterol, therefore this study aimed to explore the effect of ARL4C on the resistance of ovarian cancer (OVC) to Carboplatin. This study collected OVC tissue samples from patients who are sensitive or resistant to carboplatin, and established Carboplatin-resistant OVC cell lines, OVCAR3(R) and SKOV3(R) using OVCAR3 and SKOV3. High throughput sequencing was conducted to find genes that regulated by ARL4C. Cholesterol esterification was performed to evaluate the transport of cholesterol from Lysosome (LY) to Endoplasmic reticulum (ER). The fluorescence of LC3-GFP-mRFP was used to evaluate the function of autophagy flux. As indicated by PCR, western blot and Immunohistochemistry, ARL4C was increased in the Carboplatin-resistant OVC tissues and cells. Knockdown of ARL4C attenuated the resistance of OVCAR3(R) and SKOV3(R) to Carboplatin. By suppressing Notch signal, ARL4C knockdown inhibited the transcriptional function of RBP-Jκ and RBP-Jκ-induced H3K4Me3, which collectively reduced OSBPL5 expression. OSBPL5 deficiency inhibited the transport of cholesterol from LYs to ER, which led to the accumulation of cholesterol in LYs and the dysfunction of autophagy. In summary, ARL4C knockdown attenuated the resistance of OVC to Carboplatin by disrupting cholesterol transport and autophagy. This study revealed a promising target to attenuate the resistance of OVC to Carboplatin and elucidated the potential mechanism.